Rozwiąż równanie:

e) 3(x + 3) = 2(x + 4) + x + 1
f) 4(3x + 2) + 5(2x + 3) = -(2x + 13)
g) 4(x - 2) - 2(x - 4) = 5(x+1) - 3x
h) 2(x - 4) = 2(2x - 1) + 6(x+1)


Odpowiedzi:
e) równanie tożsamościowe
f) x= -1,5
g) równanie sprzeczne
h) x= -1,5

Robię i mi wychodzą inne wyniki ;DD

2

Odpowiedzi

2010-03-02T15:38:27+01:00
E) 3(x+3)=2(x+4)+x+1
3x+9=2x+8+x+1
0=0 równanie tożsamościowe

f)4(3x + 2) + 5(2x + 3) = -(2x + 13)
12x+8+10x+15=-2x-13
24x=-36/:24
x=-1,5

g) 4(x - 2) - 2(x - 4) = 5(x+1) - 3x
4x-8-2x+8=5x+5-3x
0=5 równanie sprzeczne

h) 2(x - 4) = 2(2x - 1) + 6(x+1)
2x-8=4x-2+6x+6
-8x=12/:-8
x=-1,5
Najlepsza Odpowiedź!
2010-03-02T15:49:32+01:00
E) 3(x+3)=2(x+4)+x+1
3x + 9 = 2x +8 +x +1
3x + 9 = 3x + 9
3x -3x = 9 - 9
0=0
Równanie tożsamościowe

f) 4(3x + 2) + 5(2x + 3) = -(2x + 13)
12 x + 8+10 +15 =-2x-13
22x +2x = -13 - 23
24x=-36 / : 24
x = -1,5

g) 4(x - 2) - 2(x - 4) = 5(x+1) - 3x
4x - 8 - 2x +8 = 5x +5 - 3x
2x = 2x + 5
2x-2x= 5
0= 5
równanie sprzeczne
h) 2(x - 4) = 2(2x - 1) + 6(x+1)
2x - 8 = 4x -2 + 6x +6
2x - 8 = 10 x + 4
2x- 10 x = 4+8
-8 x = 12 / :(-8)
x= -1,5